The Burden of HIV-Associated Dementia in Acquired Immunodeficiency Syndrome: A Case-Control Study - Asekomeh, God'spower Eshiofe; Onwuchekwa, Arthur C.; Ogunrin, Olubunmi A. (Journal of Neurology and Epidemiology, 2013)
Objectives: The prevalence of HIV dementia in West Africa is poorly defined. Hence we sought to determine the frequency of HIV-associated dementia in advanced HIV-1 infection and assess the contributory role of HIV-2 co-infection and other risk factors in a Nigerian population. Subjects and Methods: A total of 130 HIV seropositive patients with CD4+ T lymphocytes count <200 cells/µl were compared with 130 age- and sex-matched healthy controls. Detailed clinical evaluation and cognitive assessment for dementia using the International HIV Dementia Scale (IHDS) were carried out on all participants. Results: The life-time prevalence of dementia in HIV- positive patients was 66.2%. The HIV-positive patients had lower scores in all cognitive domains of the IHDS (p<0.05). Reduced mean score of Karnofsky performance scale, reduced body mass index, reduced total lymphocyte count and CD4+ T-lymphocyte cell count increased risk of dementia but HIV-2 co-infection was not associated with development of dementia. Conclusion: There is a high burden of dementia among Nigerian adults with HIV/AIDS. This underscores the need for regular cognitive assessment for early detection and institution of appropriate intervention.